Mode-locked thulium doped fiber laser with zinc oxide saturable absorber for 2 μm operation - Ahmad, Harith; Samion, Muhamad Zharif; Kamely, A.A.; Ismail, Mohammad Faizal (Elsevier, 2019)
In this work, a 2.0-µm mode-locked thulium doped fiber laser is demonstrated using zinc oxide (ZnO) as the saturable absorber (SA) in a thulium doped fiber laser (TDFL). The ZnO nanorods was prepared by the facile hydrothermal method, and then embedded in polyethylene oxide composite film to form the SA. The laser is capable of generating soliton pulses at a central wavelength of 1945.45 nm with a 3-dB bandwidth of 3.47 nm. The pulse width is measured to be 1.395 ps, only slightly higher than the calculated transform-limited pulse width of 1.15 ps. The peak power of the generated mode-locked pulses is then calculated to be as high as 41.88 W, with a signal-to-noise ratio of 50.5 dB. The fabricated ZnO film in this work would allow the generation of mode-locked pulses, which could be useful for applications in spectroscopy and medicine due to the eye-safe and highly sensitive nature of the 2.0-µm region.